Study of Mental Stress Related with Lifestyle During COVID-19: A Case Study of Bangladesh - Fahim, Ashraf; Liza, Suraiya; Lina, Sunjida; Salim, Md. Adnan (International Journal of Education and Cognitive Sciences, 2022)
An outbreak of new coronavirus pneumonia occurred in December 2019 in Wuhan, China. Former infectious disease outbreaks have significantly affected individuals’ mental health along with the expected physical health outcomes. This paper attempted to explore the actual mental health condition of the mass people and its effect on their lifestyle in terms of some demographic factors and their activities which were hampered by the COVID-19. This study was a cross-sectional, observational study carried out in Bangladesh. The online questionnaire developed by the investigators contained a total of four sections related to personal information, family related information, mental stress due to COVID-19, and lifestyle affected by COVID-19. Mental stress because of the COVID-19 contained 11 items, and the effect of mental stress related to lifestyle contained 16 items. Participants rated them in a 5-point Likert scale format. Statistical analyses like Bar Graph, table, Pearson correlation were performed using Excel 2016. Findings indicate that nearly 52% of the respondents reported high stress, 19% of respondents reported moderate stress, and 29% of respondents were in less stress due to COVID-19 while we collected the data. Maximum working people were mostly concerned about their job, income, and education. Almost 32% of respondents attempted to leave their residence. On the other hand, 17% of respondents had a plan to go back to their village. The COVID-19 outbreak created fear and stress on Bangladeshi citizens. We found that the mental stress of the respondent hampered their job life and education, accommodation, daily life activities, and attitude.